2008
DOI: 10.1158/0008-5472.can-08-1401
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Silencing of Nuclear Factor Erythroid-2–Related Factor 2 Gene Expression in Non–Small Cell Lung Cancer Inhibits Tumor Growth and Increases Efficacy of Chemotherapy

Abstract: Nuclear factor erythroid-2 related factor-2 (Nrf2) is a redox-sensitive transcription factor that regulates the expression of electrophile and xenobiotic detoxification enzymes and efflux proteins, which confer cytoprotection against oxidative stress and apoptosis in normal cells. Loss of function mutations in the Nrf2 inhibitor, Kelch-like ECH-associated protein (Keap1), results in constitutive activation of Nrf2 function in non-small-cell lung cancer (NSCLC). In this study, we demonstrate that constitutive a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
321
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(351 citation statements)
references
References 47 publications
26
321
1
3
Order By: Relevance
“…Recently an exciting report by Singh et al showed that siRNA-mediated silencing of nuclear factor erythroid-2-related factor 2 gene expression in non-small cell lung cancer inhibited tumor growth and increased efficacy of chemotherapy (Singh et al, 2008). Therefore, identification and silencing of genes related to the growth and survival of lung cancer cells would be an interesting area of research.…”
Section: Silencing Of the Cops3 Gene By Sirna Reduces Proliferation Omentioning
confidence: 99%
See 1 more Smart Citation
“…Recently an exciting report by Singh et al showed that siRNA-mediated silencing of nuclear factor erythroid-2-related factor 2 gene expression in non-small cell lung cancer inhibited tumor growth and increased efficacy of chemotherapy (Singh et al, 2008). Therefore, identification and silencing of genes related to the growth and survival of lung cancer cells would be an interesting area of research.…”
Section: Silencing Of the Cops3 Gene By Sirna Reduces Proliferation Omentioning
confidence: 99%
“…The number of lung cancer patients are increasing annually. Therapeutic approaches, such as chemotherapy, radiotherapy, and surgery have been widely used to treat lung cancer; however, these treatments offered little survival rate due to severe toxicity and drug resistance (Broker et al, 2002;Singh et al, 2008). Therefore, understanding of the carcinogenic mechanisms and genes involved in lung cancer cell's fast growth is of much importance in developing more precise treatments compared to conventional treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have shown that the Nrf2-Keap1 pathway protects cells from many diseases including neurodegenerative disease and cancers [10,11]. Recently, several studies indicated that activation of Nrf2 is associated with tumorigenesis and resistance of chemotherapeutics in lung cancer, colon cancer, prostate cancer, and type II endometrial cancer [12][13][14][15]. Elevated expression of Nrf2 and its downstream genes contributed to MCF-7-derived tamoxifen resistance cell line, and using Nrf2 siRNA to block the expression of Nrf2 can reverse resistance of the cell lines to tamoxifen [16].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, overexpression of Nrf2 in cancer cells that have low basal levels of Nrf2, enhanced resistance in a variety of cancer cells including neuroblastoma, breast, ovarian, prostate, lung, and pancreatic cancer cells (28)(29)(30)(31)(32). Combined use of Nrf2-siRNA and carboplatin inhibited the growth of A549 xenografts in mice (33). In addition, we have demonstrated that suppression of Nrf2 by Keap1 overexpression sensitized SPEC-2 cells, which are derived from type II endometrial cancer, and SPEC-2 xenografts to cisplatin (27).…”
mentioning
confidence: 99%